Electronic Payment: A Determinant of Tax Revenue Generation in Nigeria: Electronic Payment: A Determinant of Tax Revenue Generation in Nigeria - Saadu, Yahaya; Inuwa Danmalam, Muhammad (Journal of Public Administration and Government, 2025)
This study seeks s to ascertain the effect of E-payment on Tax revenue generation in Nigeria, using Federal Inland Revenue Service (FIRS) as unit of analysis. Open Innovation theory it has been used to underpin the study. Sequential mixed method is employed and adopted; data were generated from both primary and secondary sources; descriptive and inferential statistics were used with the aid of SPSS version 23.0. It has been discovered that e-payment has positive and significant relationship with revenue generation of Federal Inland Revenue Service in Nigeria. This indicates that FIRS use electronic means in collecting revenue such credit cards i.e master card, visa card and verve card, and point of sale (POS) etc. Consequently, the study recommends that FIRS should to maintain the existing processes of e-payment of revenue such as credit cards; master card, verve card and visa card, and come up with advance additional initiative for revenue generation such as application software, which taxpayers can download and use in paying their entitlement/taxes. This would strengthen e-payment conveniences, viability, reliability, and above all FIRS reputation.